Respect: a value that challenges the education of tabasquean university students in liquid modernity - Hernández Romero, Gladys (2020)
Values are considered a guide or pattern of behavior that guides the particular ways of being and living of the individual. Furthermore, they form the criteria of judgment, preference and choice that lead to a certain action. In this sense, the objective of this research is to know the practice of values during the professional training of university students, prioritizing respect. For data collection, a self-made questionnaire of eight items was applied to an intentional sample of 100 students, with ages ranging from 18 to 20 years old, within a public university located in the south-southeast of the United Mexican States. The results indicate that the participants consider practicing the values; however, these outcomes powerfully attract attention, since in counterpart they manifest the lack of ethical practices in daily coexistence within the academic institution. Among the conclusions, the need to establish actions that reduce the presence of conflicts in academic life and professional relationships is pointed out, thus forming an ethical environment for the future generation of work.